ULTRASTRUCTURE OF ISOLATED KIDNEY MITOCHONDRIA TREATED WITH PHLORIZIN AND ATP - Burgos, Mario H. (The Rockefeller University Press, 1964)
Direct electron microscopic evidence is reported of the ultrastructure of mitochondrial membranes and compartments in mitochondria isolated in 0.5 M sucrose from the rat kidney cortex and the experimental changes they undergo with phlorizin and ATP treatment. A heterogeneous population of mitochondria is recognized under control conditions. The mitochondria appear to be of 3 main types, normal, swollen, and contracted. Under phlorizin treatment, most of the mitochondria swell in less than 15 minutes, apparently at the expense of the matrix. Treatment with ATP, on the other hand, produces, during the same time, a marked contraction of the isolated mitochondria, with many refoldings of the inner membrane and marked increase in the electron opacity of the matrix. It is concluded from these observations that mitochondrial swelling and contraction should be related mainly to the matrix content.